Stress und Belastung bei Personen im diplomatischen Dienst (Stress and burden in diplomatic service). - Galindo, Edgar (2017)
This paper describes working and living conditions of persons within diplomatic services from the perspective of stress and demands. The conditions of stress and demands described in this article are similar for leaders, volunteers, actors of international agencies and nongovernmental organizations. Scope and diversity of diplomatic tasks and connected psychsocial stress will be outlined. Families of diplomates are also affected. Mental health problems in the diplomatic corps are known, but they are considered as a taboo issue. Consequently, the basis of empirical research and literature is limited. It is mentioned that expatriates, migrants, refugees and students in foreign countries can develop similar problems. The role of psychology and psychotherapeutic interventions are discussed.